Oral health status of 6- to 12-year-old children in Madrid, Spain: A cross-sectional study. Issue 6 (June 2022) - Adanero, Alberto; Baquero, Lucía; Berasategui, María; Velayos, Laura; Espí, Miguel; Piñeiro, Marta; Miegimolle, Mónica
Abstract: Based on the results of the 2015 oral health survey in Spain, the prevalence of untreated dental caries in temporary dentition, in the six-year cohort was 27, 8%, and in the twelve-year cohort 14, 6%. Due to the magnitude of the problem, the high health cost and the possibilities of prevention, monitoring the oral health status of the child population is extremely important, as it will allow the implementation of prevention and early care strategies. Objectives: To study the caries prevalence and malocclusion in the mixed dentition in children aged 6–12 years in Madrid, Spain. . Materials and methods: This is a descriptive, cross-sectional study carried out in the city of Madrid during the 2018–2019 school year. Fifth year students of the European University of Madrid through health surveys, calibrated and supervised by the two main researchers, collected the data. The schoolchildren assessed were students from different schools in the city of Madrid, between 6 and 12 years old. According to WHO standards, data were collected in 2 months. Results: The total number of students examined was 303 students from 4 different schools in the community of Madrid. The prevalence of caries in our sample in the primary dentition was 45.21% with dmf> 0 and in the permanent dentition it was 23.7 % with a DMF> of 0. Conclusions: The oral health survey carried out in the sample shows a high prevalence of caries, as well as in the dmf and DMF indicators. Most of the children needed fluoride applications, so it would be interesting to evaluate which of them can be prevented with different public health projects. Abstract : Caries, Schoolchildren, Oral health, Malocclusion and epidemiology survey.